Behavioural Assessment Perspective on Reward System Management and Performance: An Empirical Finding on Indonesian Lecturer - Wahyono, Wahyono; Prihandono, Dorojatun; Wijayanto, Andhi (JDM (Jurnal Dinamika Manajemen), 2018)
The role of this research is to get a clearer picture of how remuneration system influence lecturer and employee performance moderates by motivation, specifically in the state universities. This study commenced in 3 major state universities in Central Java Indonesia in order to have Structural Equation Modelling (SEM) method was applied to examine and analyse the relationships between determinants. The results of this study show that ‘performance feedback’ has negative effect on ‘competence’; the relationship between ‘competence’ and ‘motivation’ is negative;‘remuneration’ positively affects ‘motivation’; the greater the level of remuneration, the greater the level of working performance intention in the institutions’;and there is positive and significant relationship between ‘motivation’ and ‘performance intention’. The study provides the importance of how the remuneration system can be applicated as one focal scheme to enhance instituions performance in general, especially applied to college.